Extracorporeal photopheresis after heart transplantation. (August 2014) - Barten, Markus J; Dieterlen, Maja-Theresa
The addition of extracorporeal photopheresis (ECP) to a standard immunosuppressive drug therapy after heart transplantation in clinical studies has shown to be beneficial, for example, by reducing acute rejection, allograft vasculopathy or CMV infection. However, the protocols varied considerably, have a predetermined finite number of ECP treatments and adjuvant immunosuppressive regimens used in combination with ECP have differed significantly. Furthermore, there are scarce data to guide which patients should be treated with ECP and when or who would benefit further if ECP were to be continued long term to increase the safety by reducing immunosuppressive drug toxicities without losing efficacy. The knowledge of the tolerance-inducing effects of ECP-like upregulation of regulatory T cells and of dendritic cells may allow to develop a strategy to monitor immunomodulation effects of ECP to further identify ECP responders, the optimal individual ECP schedule and whether ECP therapy can replace or reduce immunosuppressive drug therapy.